Serum Anti-Müllerian Hormone Levels Were Negatively Associated With Body Fat Percentage in PCOS Patients - Luo, Er; Zhang, Jinxiao; Song, Jiahui; Feng, Di; Meng, Yaxin; Jiang, Hongyu; Li, Da; Fang, Yuanyuan (Frontiers in Endocrinology, 2021)
Background: Obesity is a state of excess body fat accumulation, and appears to be closely associated with polycystic ovary syndrome (PCOS). Notably, plausible biological pathways through which obesity can regulate anti-Müllerian hormone (AMH) production have been proposed, and women with PCOS characteristically have an increased AMH level. Body fat accumulation can be described by body fat percentage (BFP). However, the relationship between BFP and AMH still remains unclear. Materials and methods: A total of 87 controls and 156 PCOS patients were divided into lean and overweight/obese groups, and the PCOS patients were further divided into hyper-AMH and normal-AMH subgroups. Univariate regression was used to assess the unadjusted relationship between AMH and outcome variables, multivariable regression analysis was performed to test whether and how serum AMH levels were associated with BFP after adjusting for other co-variables. Receiver-operating characteristic (ROC) curve analyses were used to test the utility of BFP for the diagnosis of PCOS. Results: BFP was higher in PCOS patients compared with controls, regardless of obesity. Serum AMH levels were negatively associated with BFP in the PCOS group (r = -0.371; P < 0.001) but not in the control group (r = -0.095; P = 0.385). Multivariable logistic regression analysis showed that elevated BFP was associated with a high risk of PCOS (odds ratio, 1.290; 95% confidence interval, 1.084–1.534, P = 0.004). Furthermore, the combination of BFP and serum AMH into a multivariate model gave an improved area under the curve (AUC) of 88.5%, with a sensitivity of 72.4% and specificity of 87.4%; the positive and negative predictive values were 91.2% and 63.9%, respectively. One limitation of this study is all the conclusion reported was based on small sample size. Conclusions: Herein, we described the negative correlation between BFP and serum AMH levels for the first time, and the present results highlight the importance of further investigation into the role of BFP, especially in body fat-related AMH change as it relates to the underlying pathogenesis of PCOS.